The effect of proliferative hypertrophic scars on determining treatment options for preventing recurrence of vesicourethral anastomotic stenosis after radical prostatectomy: a single-center cross-sectional study - Selvi, Ismail; Arik, Ali Ihsan; Basay, Mehmet Sinan; Basar, Halil (São Paulo Medical Journal, 2021)
BACKGROUND: Vesicourethral anastomotic stenosis (VUAS) following retropubic radical prostatectomy (RRP) significantly worsens quality of life. OBJECTIVES: To investigate the relationship between proliferative hypertrophic scar formation and VUAS, and predict more appropriate surgical intervention for preventing recurrent VUAS. DESIGN AND SETTING: Retrospective cross-sectional single-center study on data covering January 2009 to December 2019. METHODS: Among 573 male patients who underwent RRP due to prostate cancer, 80 with VUAS were included. They were divided into two groups according to VUAS treatment method: dilatation using Amplatz renal dilators (39 patients); or endoscopic bladder neck incision/resection (41 patients). The Vancouver scar scale (VSS) was used to evaluate the characteristics of scars that occurred for any reason before development of VUAS. RESULTS: Over a median follow-up of 72 months (range 12-105) after RRP, 17 patients (21.3%) had recurrence of VUAS. Although the treatment success rates were similar (79.5% versus 78.0%; P = 0.875), receiver operating characteristic (ROC) curve analysis indicated that dilatation using Amplatz dilators rather thanendoscopic bladder neck incision/resection in patients with VSS scores 4, 5 and 6 may significantly reduce VUAS recurrence. A strong positive relationship was observed between VSS and total number of VUAS occurrences (r: 0.689; P < 0.001). VSS score (odds ratio, OR: 5.380; P < 0.001) and time until occurrence of VUAS (OR: 1.628; P = 0.008) were the most significant predictors for VUAS recurrence. CONCLUSIONS: VSS score can be used as a prediction tool for choosing more appropriate surgical intervention, for preventing recurrent VUAS.